2016
DOI: 10.1515/meceng-2016-0003
|View full text |Cite
|
Sign up to set email alerts
|

Multiresponse Optimization of Edm Process with Nanofluids Using Topsis Method and Genetic Algorithm

Abstract: Electrical Discharge Machining (EDM) process with copper tool electrode is used to investigate the machining characteristics of AISI D2 tool steel material. The multi-wall carbon nanotube is mixed with dielectric fluids and its end characteristics like surface roughness, fractal dimension and metal removal rate (MRR) are analysed. In this EDM process, regression model is developed to predict surface roughness. The collection of experimental data is by using L9 Orthogonal Array. This study investigates the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…A multi-objective optimization of EDM process parameters for AISI D2 steel was performed using TOPSIS [7]. The results indicated that S/N of the ranking index determined the optimal set of process parameters, and were different from those of the index ranking.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A multi-objective optimization of EDM process parameters for AISI D2 steel was performed using TOPSIS [7]. The results indicated that S/N of the ranking index determined the optimal set of process parameters, and were different from those of the index ranking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In several studies, these combinations have been arbitrarily chosen, without considering the suitability of the Taguchi method with other methods by S/N of ranking index. Also, the weights of the criteria in many of the works are determined by empirical research, and this has led to the effectiveness of optimized results that have a scope limited to practical applications [31]. In the multi-objective optimization problem, it is essential to determine the value of the weight of quality criteria accurately and to see that it is appropriate for practical purpose.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…2.1. TOPSIS Theory [1][2][3][4][5][6][7][8] TOPSIS (Technique for Order Preference by Similarity to an Ideal Solution). It is based on the normalization after the original data matrix, finding the optimal solution and the worst in this limited solution scheme (with the optimal vector and the worst vectors, resp.…”
Section: The Theory Of Topsis Factor Analysis Modelmentioning
confidence: 99%
“…It can be used for optimizing material removal rate, electrode wear and surface roughness responses in PMEDM (Tripathy & Tripathy, 2017). Material removal rate (MRR), surface roughness and fractal dimension are also responses to optimize when machining AISI D2 tool steel (Prabhu & Vinayagam, 2016;Zerti et al, 2018). The results showed that voltage has the strongest effect (42.42 %) and pulse on time has the smallest effect (11.13%).…”
Section: Introductionmentioning
confidence: 99%